The Effect of Quartz Particle Size on the Frictional and Electrically Conductive Properties of Mixed Graphite–Quartz Gouges - Chen, Jinyu (Frontiers in Earth Science, 2022)
Mature faults usually contain fault rocks with a wide range of mineral grain sizes. Despite the importance of mineral grain sizes in affecting fault slip behaviors, little is known about the potential mechanism(s). To better understand this problem, electrical conductivity measurements on synthetic carbon-bearing gouges were conducted along a fault-parallel direction under progressive fault slip. All experiments were carried out under a slip rate of 1 mm/s, a normal stress of 2 MPa, ambient temperature, and a pure N2 atmosphere. The specimens that were used were mixtures of identical 6 wt.% graphite (Gr) powders and 94 wt.% quartz (Qz) particles with five different particle sizes (#100~12500 mesh). As Gr has a low friction coefficient and high electrical conductivity, the approach in this study may provide a favorable opportunity to examine the relation between the evolution of friction and shear textures. Experimental results indicate that the reduction in Qz particle sizes causes gradual segregation of the Gr powders in the skeletal frame formed by granular Qz particles, resulting in the decreased interconnectivity of the anastomosing Gr-film networks and the destruction of Gr-lubricated slip surface(s). Then, it eventually manifests as an increase in the steady-state frictional coefficient (μss) and a logarithmic decrease in the steady-state electrical conductivity (σss) for Gr-bearing specimens. Furthermore, the Gr-bearing gouges containing > 3 μm Qz particles first develop foliated layers, and subsequent Gr films penetrate around the boundary of the Qz particles to form conductive interconnected networks during a progressive fault slip. These experimental results imply that carbonaceous materials (CMs) represented by Gr may complicate the frictional properties of fine-grained fault gouges in mature faults.